KUALITAS MADU LOKAL DARI LIMA WILAYAH DI KABUPATEN WONOSOBO - Rofiqotul Khasanah; Sarjana Parman; Sri Widodo Agung Suedy (Jurnal Akademika Biologi, 2017)
Honey is sweet natural substance produced by honey bees (Apis sp.) from the nectar or other parts of plant. The nutritional content influences its quality. The contents are sugar, then water, and also some of organic acids. The purpose of this research is to analyse the honey quality from its water content, acidity, and sugar content in local honey from Wonosobo Regency. The samples were taken in the five locations, i.e Topengan village (TP), Pringapus (PA), Kalikuning (KK), Krinjing (KJ), and Mutisari (MS). The data analysis with ANOVA test (α = 5%). The Standardisation's reference of honey quality based on Indonesia National Standardisation (SNI) 2013 and EC Directive in 2001 year. The Results were water content was 22.17 - 23.67%, acidity was 34.08 - 39.37 ml NaOH/ kg, and sugar content was 74.83% - 76.17%. All samples were in low quality, except PA that was in standard with water content was 22,17%, acidity was 34,08 ml NaOH/kg, and sugar content was 76,17oBx. Keywords: honey quality, water content, acidity, and sugar content